Factors Affecting Profit Management In Manufacturing Companies Listed On The Indonesia Stock Exchange Year 2018 – 2020 - Ni Luh Gde Novitasari; Ni Luh Putu Sandrya Dewi; Komang Suarjana (JUSTBEST: Journal of Sustainable Business and Management, 2022)
The company performs earnings management to intervene in the process of preparing financial statements. Investors' view of a company is influenced by company size, managerial ownership, institutional ownership, profitability, and leverage. The aim is to examine the effect of firm size, managerial ownership, institutional ownership, profitability, and leverage on the earnings management of manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The sample is 42 companies with purposive sampling method and using multiple regression analysis technique. The results of this study indicate that firm size has a negative effect on earnings management. Profitability has a positive effect on earnings management. Meanwhile, managerial ownership, institutional ownership, and leverage have no effect on earnings management.